CUSTOMER LOYALTY AND PASSENGER SATISFACTION ON LION AIR’S LOW COST CARRIER - Rezty Fauziah Novianty; Juliater Simamarta; Dinar Dewi Kurnia; Jermanto Setia Kurniawan (Journal of Business Studies and Management Review, 2021)
This study aims to determine the effect of ticket price and service quality on customer loyalty through passenger satisfaction as an intervening variable on the Low Cost Carrier (LCC ) of Lion Air airlines. Low Cost Carrier airlines which have relatively cheap ticket price, but due to the economic crisis in Indonesia, these air transportation services are relatively expensive compared to the previous year, which according to the Indonesian National Air Carrier Association, the increase reached almost 40-120% for each airline, because the increase that occurred made LCC airlines, especially Lion Air, experience a very drastic decrease in passengers by 35% in 2019, apart from ticket price increases, the quality of service provided by lion air airlines is also still not good so that passengers are not satisfied with Lion Air airlines. This research was conducted at Soekarno Hatta International Airport. The study was conducted using quantitative methods, with a sample of 100 respondents and data were taken using a questionnaire and processed using smart-PLS 3. The results of this study are from 7 proposed hypotheses, 6 of which are accepted and 1 of the hypothesis is rejected, for the rejected hypothesis is the effect of ticket price on the loyalty of Lion Air airline passengers.